2003
DOI: 10.1161/01.str.0000102044.27905.b5
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness Measurements in Intervention Studies

Abstract: Background-Carotid intima-media thickness (CIMT) measurements are currently widely used in randomized controlled trials (RCTs) to study the efficacy of interventions. In designing a RCT with CIMT as a primary outcome, several ultrasound options may be considered. We discuss the various options and provide a pooled estimate of CIMT progression. In addition, we quantify the effect of these choices on the sample size for a RCT. Summary of Comment-To estimate the average CIMT progression rate, we performed a poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
1
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 321 publications
(126 citation statements)
references
References 115 publications
4
116
1
5
Order By: Relevance
“…Using carotid intimal medial thickness measurements as a surrogate efficacy end-point, Bots et al reported that 468 patients would be required to detect a treatment effect of 30% (power 0.80) (33). Three-dimensional ultrasound of plaque in the carotids would require fewer patients to demonstrate efficacy, yet a recent study reported that 203 patients would still be needed to detect a 10% change in plaque volume (power = 0.90) measured over a three month period (34).…”
Section: Discussionmentioning
confidence: 99%
“…Using carotid intimal medial thickness measurements as a surrogate efficacy end-point, Bots et al reported that 468 patients would be required to detect a treatment effect of 30% (power 0.80) (33). Three-dimensional ultrasound of plaque in the carotids would require fewer patients to demonstrate efficacy, yet a recent study reported that 203 patients would still be needed to detect a 10% change in plaque volume (power = 0.90) measured over a three month period (34).…”
Section: Discussionmentioning
confidence: 99%
“…The end-diastolic intima-media thickness (IMT) of the far wall of the middle segment of both common carotid arteries, defined by a simultaneous electrocardiographic recording, was measured 1 cm caudal to the bulb, as the distance between the lumen-intima interface and the media-adventitia interface. 13,14 Each measurement was calculated by taking the average of three readings. Intima-media thickening of the common carotid arteries was defined as an average IMT X0.9 mm.…”
Section: Carotid Ultrasonographymentioning
confidence: 99%
“…Other recent studies demonstrated that the association between near-wall CIMT and stroke or MI was as strong as that found for far-wall CIMT, and near-wall CIMT measurement can be obtained with sufficient reproducibility in a considerable proportion of the participants. 18 The combined CIMT measurements of near and far walls showed the strongest association, and may enhance precision without loss of validity. 16 In summary, although most of the carotid lesions locate at CB, the combined measurement of IMT at CCA, CB and ICA shows the most significance in prevalent cardiovascular events.…”
Section: Methods Of Cimt Measurementmentioning
confidence: 91%
“…In some researches, CCA-IMT has shown to predict future cardiovascular events as well as mean CIMT. 18 Results from the Pravastatin, Lipids, and Atherosclerosis in the Carotid Arteries II even showed that IMT at the far wall of CCA was significantly correlated with progression or regression of disease other than the aggregate measurements at near and far walls of CCA, CB and ICA. 19 However, the CHS, the Rotterdam study and some other studies showed that CB-IMT was more closely related to coronary atherosclerosis, existing atherosclerotic diseases and major established risk factors compared with CCA-IMT.…”
Section: Methods Of Cimt Measurementmentioning
confidence: 97%
See 1 more Smart Citation